Capabilities of public administration systems for the prevention and resolution of ethnic conlifcts - Jibgashvili, Zurab (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The presented article „Possibilities of thegovernment state systems for the prevention and resolution of ethnic conflicts“ examines modern theories that exist with the aim of integrating a multinational society. The article formulates the problems and highlights those important aspects that act as influential factors, and the agreements around which directly determine the harmonization of the system of the government with the ethnic composition of society, with the aim of its implementation and integration. The paper examines the mechanisms of atypical influence - the characteristics of the electoral system, ethnic veto, ethnic coalitions, the rule of electing the president, the collegial head of state, etc. - on a typical system of government,based on consensus, conditioned on the diversity of society.